Sr1.8Nd1.2Mn2O7: Synthesis, crystal structure, and physical properties - Battle, P; Hepburn, J; Millburn, J; Radaelli, P; Rosseinsky, M; Spring, L; Vente, J (1997)
A detailed investigation into the preparation of powder samples of the n = 2 Ruddlesden-Popper (RP) oxide Sr1.8Nd1.2Mn2O7 is presented. This material is of interest as it displays colossal magntoresistance (CMR) without three-dimensional ferromagnetic long-range order. It is shown that Rietveld refinement of high-resolution powder X-ray and neutron diffraction data is essential to assess the outcomes of syntheses because of the potential coexistence of two very similar Ruddlesden-Popper phases. Phase coexistence or significant temperature-dependent anisotropic strain can be indicated by the broadening of the {0 0 10} reflection at 5 K. This suggests that a more subtle form of the previously reported phase separation at x = 0 is also difficult to avoid at the x = 0.2 composition. Precise attention to reaction temperature and time is required to prepare samples containing only one n = 2 Ruddlesden-Popper phase, and contamination by small quantities of the n = ∞ perovskite is a pervasive problem. Neutron powder diffraction structural analysis of the highest quality sample allows a comparison with the three-dimensional ferromagnet Sr1.8La1.2Mn2O7. The structure suggests that only slight changes in the Mn-O bond lengths are required to radically alter the electronic structure of n = 2 Ruddlesden-Popper phases.